Антропоморфний вимір сучасних національних гранд - наративів - Зашкільняк, Л. (Інститут історії України НАН України, 2008)
The characteristic feature of the national narrative construction always remains the representation of every community as the person with all human attributes. This “person” develops in time and space, lives and suffers, contacts with other communities like the alone man. The similar construction of national narratives causes formation of national stereotypes, which from one side strengthens the community, but from another – forms negative attitude to other and different communities. The result of national narrative construction always is the idealization of own community and the mutilation of other one.